Modeling the political choice of public health insurance - Fall, Abdou Khadre Dit Jadir (Frontiers in Applied Mathematics and Statistics, 2023)
This paper studies the choice between two health insurance systems in a monopolistic scheme. The first proposes a uniform contribution level and the second proposes a contribution proportional to the probability of getting sick. Individuals differ by their number, income, contribution and risk. Two kinds of voting models using welfare function are used; a direct vote which involves a size effect and a probabilistic vote which involves a bias in favor of one system Results, according to theorical models, indicate that a uniform contribution level is adopted by high-risk individuals and also if wealth and illness are strongly negatively correlated. However, when wealth and illness are not correlated or poorly correlated, a contribution proportional to the probability of getting sick system is adopted. These results are explained by the fact that the loss of well-being for low-income and sick people is more important.